2016
DOI: 10.1039/c6cc06794h
|View full text |Cite
|
Sign up to set email alerts
|

A chiral pool approach for asymmetric syntheses of (−)-antrocin, (+)-asperolide C, and (−)-trans-ozic acid

Abstract: Ozonolysis of aromatic abietane (+)-carnosic acid (4) is used to create an important intermediate in an enantiomerically pure form, resulting in a simple, concise, readily scalable, and asymmetric synthesis of (-)-antrocin (1). This strategy not only provides an efficient approach to (-)-antrocin (1) synthesis but can also be readily adopted for the syntheses of optically pure (+)-asperolide C (2) and (-)-trans-ozic acid (3) from the naturally abundant aromatic abietanes (+)-podocarpic acid (5) and (+)-dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Yang et al [20] reported the synthesis of (±)-antrocin by using Au(III)-catalyzed tandem reaction as a key step. The same group also reported [21] the synthesis of (−)-1 from naturally occurring carnosic acid as a chiral pool. Although carnosic acid possesses the appropriate stereocenters for the synthesis, however, their higher manufacturing cost and poor availability limit further development.…”
Section: Introductionmentioning
confidence: 97%
“…Yang et al [20] reported the synthesis of (±)-antrocin by using Au(III)-catalyzed tandem reaction as a key step. The same group also reported [21] the synthesis of (−)-1 from naturally occurring carnosic acid as a chiral pool. Although carnosic acid possesses the appropriate stereocenters for the synthesis, however, their higher manufacturing cost and poor availability limit further development.…”
Section: Introductionmentioning
confidence: 97%
“…The aforementioned highly enantioselective phosphine‐catalyzed (3+2) cyclization between isoindogos and allenes allows quick creation of challenging bisindoline alkaloid core structures, which are amenable for further synthetic transformations (Scheme ). The spirocyclic annulation product 3 a (99 % ee ) was subjected to ozonolysis, and then decarboxylation took place to afford bisoxindole 7 . The subsequent acetal formation and allylation afforded 8 in high yield.…”
Section: Methodsmentioning
confidence: 99%
“…Thespirocyclic annulation product 3a (99 % ee)w as subjected to ozonolysis, [14] and then decarboxylation took place to afford bisoxindole 7.T he subsequent acetal formation and allylation afforded 8 in high yield. Thespirocyclic annulation product 3a (99 % ee)w as subjected to ozonolysis, [14] and then decarboxylation took place to afford bisoxindole 7.T he subsequent acetal formation and allylation afforded 8 in high yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thea forementioned highly enantioselective phosphinecatalyzed (3+ +2) cyclization between isoindogos and allenes allows quick creation of challenging bisindoline alkaloid core structures,w hich are amenable for further synthetic transformations (Scheme 6). Thespirocyclic annulation product 3a (99 % ee)w as subjected to ozonolysis, [14] and then decarboxylation took place to afford bisoxindole 7.T he subsequent acetal formation and allylation afforded 8 in high yield.…”
Section: Angewandte Chemiementioning
confidence: 99%